Stress during pregnancy and fetal serum BDNF in cord blood at birth - Lamadé, Eva; Pedraz-Petrozzi, Bruno; Lindner, Ole; Meininger, Pascal; Coenen, Michaela; Witt, Stephanie; Rietschel, Marcella; Dukal, Helene; Gilles, Maria; Wudy, Stefan A.; Hellweg, Rainer; Deuschle, Michael (Psychoneuroendocrinology, 2024)
Introduction - Adverse environments during pregnancy impact neurodevelopment including cognitive abilities of the developing children. The mediating biological alterations are not fully understood. Maternal stress may impact the neurotrophic regulation of the offspring as early as in utero and at birth. Brain-derived neurotrophic factor (BDNF) is essential for neurodevelopment. Short-term higher levels of BDNF in mice upon stressors associate with lower BDNF later in life, which itself associates with depression in animals and humans. Stress including glucocorticoids may impact BDNF, but there is a lack of data at birth. This study investigated if stress near term associates with fetal BDNF at birth in humans. - Methods - Pregnant women near term who underwent primary cesarean sections (at 38.80±0.64 weeks), were included in this study (n=41). Stress at the end of pregnancy was assessed before the cesarean section by determining maternal depressive symptoms (EDPS), maternal state and trait anxiety (STAI-S and STAI-T), maternal prenatal distress (PDQ), stress over the past month (PSS), prenatal attachment to the offspring (PAI), maternal social support (F-Sozu), maternal early life stress (CTQ), socioeconomic status, and the glucocorticoids cortisol and cortisone (n=40) in amniotic fluid at birth. The association with fetal BDNF was analyzed. Cord blood serum of n=34 newborns at birth was analyzed for BDNF and newborn anthropometrics (weight, length and head circumference per gestational age at birth) were assessed. The association of fetal BDNF with anthropometrics at birth was analyzed. - Results - After a BDNF-outlier (>3SD) was removed, higher fetal BDNF associated significantly with maternal depressive symptoms (r=0.398, p=0.022), with lower socioeconomic status as assessed by the average number of people per room in the household (r=0.526, p=0.002) and with borderline significance with net income per person in the household (r=-0.313, p=0.087) in the bivariate analyses. In multivariable analysis, BDNF stayed positively associated with maternal depressive symptoms (β=0.404, 95% CI [7.057, 306.041], p=0.041) and lower net income per person in the household (β=-0.562, 95% CI [-914.511, −60.523], p=0.027) when controlling for maternal age, maternal pre-pregnancy BMI, fetal sex and gestational age. Fetal BDNF did not associate with newborn anthropometrics with the outlier removed in bivariate analyses or in multivariable analyses when controlling for maternal BMI and fetal sex. - Conclusion - Maternal depressive symptoms and lower socioeconomic status associated with higher fetal BDNF when controlling for confounders. Fetal BDNF did not associate with newborn anthropometrics with the outlier removed. Further studies should investigate how early altered BDNF associate with the development and possibly psychopathology of the offspring.
Online verfügbar: 27. März 2024, Artikelversion: 10. April 2024
Gesehen am 10.02.2025